Dense precipitation clusters and particle-stimulated nucleation-mediated dynamic recrystallization enabling improved strength-ductility synergy in a micro-alloyed Mg-1Zn-0.6Zr alloy - Min Yang; Fei Liu; Yuan-Biao Tan; Wei Shi; Hao Fu; Song Xiang (Materials & Design, 2025)
The broader application of Mg alloys as structural materials remains constrained by the trade-off between strength and ductility. In this study, multi-directional rolling was applied to a micro-alloyed Mg-1Zn-0.6Zr alloy, yielding a significantly enhanced yield strength (YS) of 181.9 MPa and a tensile fracture elongation (FE) of 23.1 %. Compared to the as-cast alloy, the rolled alloy exhibits a significantly greater YS by 113.6 MPa, accompanied by a marginal reduction in ductility of 3.7 %. The strength improvement is primarily attributed to grain boundary strengthening, texture strengthening, dislocation strengthening and hetero-deformation induced (HDI) strengthening. Additionally, dense precipitation clusters contribute to strengthening by acting as preferential sites for dislocation accumulation. A bimodal grain structure, formed via particle-stimulated nucleation (PSN)-mediated dynamic recrystallization, further enhances strength through grain boundary strengthening. These precipitation clusters predominantly consist of nano-scale rod-shaped ZnZr phases. This study presents a novel microstructural design strategy to achieve an improved strength-ductility synergy in Mg alloys.